The Role of Training Programs for Youth Employment in Nepal : Impact Evaluation Report on the Employment Fund - Chakravarty, Shubha; Lundberg, Mattias; Nikolov, Plamen; Zenker, Juliane (World Bank, Washington, DC, 2015)
The youth unemployment rate is exceptionally high in the developing world. Because quality of education is arguably one of the most important determinants of youth’s labor force participation, governments worldwide have responded by creating job training and placement services programs. Despite the rapid expansion of skill-enhancement employment programs across the world and the long history of training program evaluations, debates about the causal impact of training based labor market policies on employment outcomes still persist. Using a quasi-experimental approach, this report presents the short-run effects of skills training and employment placement services in Nepal. Launched in 2009, the intervention provided skills training and employment placement services for over 40,000 Nepalese youth over a three-year period, including a specialized adolescent girls’ initiative that reached 4,410 women aged 16 to 24. The authors find, after three years of the program, the EF intervention positively improved employment outcomes. EF training program participation generated an increase in non-farm employment of 15 to 16 percentage points for an overall gain of about 50 percent. The program also generated an average monthly earnings gain by about 72 percent. The authors find significantly larger employment impacts for women than for men, but younger women aged 16 to 24 experienced the same improvements as older females. These employment estimates are comparable, though somewhat higher, than other recent experimental interventions in developing countries.